Representation of “Sapa Nandur Ngundhuh” in the Wayang Performance of Cupu Manik Astagina by Ki Enthus Susmono: Representasi “Sapa Nandur Ngundhuh” dalam Pergelaran Wayang Lakon Cupu Manik Astagina oleh Ki Enthus Susmono - Ida Fariha; Sucipto Hadi Purnomo (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Wayang kulit not only functions as entertainment, but is also a vehicle for conveying philosophical messages. As in the Cupu Manik Astagina puppet play, there is a philosophical message in the form of